Carta Editorial - Dichdji, Ayelen; Franz Amaral, Márcia; Simeunović Bajić, Nataša; Donald, Rosalind; Miraglia, Marina; Dutra e Silva, Sandro (Historia Ambiental Latinoamericana y Caribeña (HALAC) revista de la Solcha, 2020)
Carta Editorial